PMP project management professional practice exams - Haner, James L. (McGraw-Hill Education, 2018)
Aligned with the current PMI Project Management Body of Knowledge (PMBOK) and the latest release of the Project Management Professional exam, PMP Project Management Professional Practice Exams provides coverage of all exam objectives and is logically organized by exam domain. All questions simulate those on the actual exam in content, style, and difficulty. To facilitate retention, every question is accompanied by in-depth explanations for both correct and incorrect answers--